2021
DOI: 10.3892/or.2021.8131
|View full text |Cite
|
Sign up to set email alerts
|

RORβ suppresses the stemness of gastric cancer cells by downregulating the activity of the Wnt signaling pathway

Abstract: Gastric cancer (GC) is the third leading cause of cancer-related mortality and the fifth most common type of cancer worldwide. GC stem cells (GCSCs) have been reported to be responsible for the malignant behavior of GC. However, the key molecular mechanism controlling GCSC function remains unclear. The present study aimed to investigate the function of retinoic acid-related orphan receptor β (RORβ) in GC. The expression levels of RORβ in GC cells and clinical GC tissues were analyzed using western blotting, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…CABP4 has been reported to be associated with the TME of urothelial carcinoma of the bladder currently (79). RORB can down-regulate the activity of Wnt signaling pathway, thus inhibiting the stemness of gastric cancer cells (82). RORB has also been found to be a prognostic marker of breast cancer (83).…”
Section: Discussionmentioning
confidence: 99%
“…CABP4 has been reported to be associated with the TME of urothelial carcinoma of the bladder currently (79). RORB can down-regulate the activity of Wnt signaling pathway, thus inhibiting the stemness of gastric cancer cells (82). RORB has also been found to be a prognostic marker of breast cancer (83).…”
Section: Discussionmentioning
confidence: 99%
“…Hyperactivation of canonical Wnt/β-catenin signaling has been reported in various cancer types including about 30–50% of GC [ 40 ], but, for the first time, we associated this pathway with the HER2-positive mGC subtype and its survival. Indeed, mounting evidence has suggested that overexpression of Wnt/β-catenin signaling not only affects gastric cell proliferation, but also the GC relapse and metastasis by giving rise to a new cancer population of stemness-associated self-renewal cells [ 41 , 42 ]. Furthermore, the self-renewal cell activity was found to increase in HER2-positive cancer stem cells via Wnt/β-catenin signaling [ 43 ] that had also been implicated in important tumor growth processes such as cell nutrient acquisition, cell metabolism, and immune response against the tumor cells [ 44 , 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many other genes affect GCSCs through WNT, NOTCH, Hedgehog, and HIPPO signaling pathways, which we have summarized in Table 1 [ 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 ].…”
Section: The Role Of Protein-encoding Genes In Gcscsmentioning
confidence: 99%